Tumpang Tindih Kewenangan Penyidikan dalam Reformasi Kitab Undang-Undang Hukum Acara Pidana dan Kejaksaan Berdasarkan Analisis Jus Constituendum - Silalahi, Frans Edward; Sari, Retno Dewi Pulung (Universitas Batanghari Jambi, 2026)
The reform of Indonesia's criminal law through the drafting of the Criminal Procedure Code Bill (RUU KUHAP) and the Prosecutor’s Office Bill (RUU Kejaksaan) has raised a serious issue concerning the overlapping authority of criminal investigation between the Indonesian National Police (Polri) and the Attorney General’s Office (Kejaksaan). While RUU KUHAP stipulates that the authority to investigate lies with the police, RUU Kejaksaan grants prosecutorial investigators the power to conduct investigations in specific cases without clear limitations. This regulatory disharmony leads to legal uncertainty, potential institutional conflicts, and the risk of abuse of power. This research is a normative juridical study using statutory and conceptual approaches. The data consist of primary legal materials such as the draft bills, relevant legislation, and secondary sources including academic journals, legal doctrines, and mainstream news reports. The analysis is conducted qualitatively with a descriptive-analytical method. The results of this study indicate that the lack of clear boundaries in investigative authority creates functional dualism and undermines the principle of due process of law. Therefore, normative and institutional reforms are necessary to emphasize functional differentiation, strengthen inter-institutional coordination, and ensure legal certainty, effective law enforcement, and the protection of human rights.